Choice of the surgical approach for patients with stage I lung squamous cell carcinoma ≤3 cm - Chen, Chunji; Wang, Yiyang; Pan, Xufeng; Fu, Shijie; Shi, Yubo; Yang, Jun; Wang, Rui (Journal of Thoracic Disease, 2018)
Background: We tried to explore the surgical procedures for stage I squamous cell carcinoma (SCC) with a size of ≤3 cm by using the Surveillance, Epidemiology, and End Results (SEER) database. Furthermore, we investigated the relationships between the chosen surgical option and the size of SCC. Methods: In total, 1,147 patient data sets were collected from 2010 to 2011 using the SEER database. Afterwards, 849 patients with a pT1–2aN0M0 SCC with a size of ≤3 cm after a lobectomy or sublobectomy procedure were identified. Kaplan-Meier curves were conducted to compare the overall survival (OS) rates and the lung cancer-specific survival (LCSS) rates between the two surgical approaches. Cox proportional hazards regressions were performed to discover the independent risk factors for both the OS and LCSS rates. Lastly, subgroup analysis was stratified by the size of the SCC and then classified by the 8th edition T category. Results: The sublobectomy procedure did not demonstrate a difference for the OS rate. Additionally, it demonstrated a worse LCSS rate when compared with a lobectomy for stage I SCC. In the subgroup analysis, a lobectomy was shown to have a better survival outcome only when the SCC was >2 and ≤3 cm. Multivariable analysis showed that a size of >2 to ≤3 cm, and an age of >60 were independently associated with poorer OS while the sublobectomy procedure and pleural invasions (PI) were related with a poorer LCSS rate. In the stratification of data for the tumor size, the cox proportional analysis still confirmed the protective effects of the lobectomy in subgroups of SCCs with sizes between >2 to ≤3 cm as well as the T1c category. Conclusions: The choice of the SCC surgery can be recommended based on the tumor size. A lobectomy procedure demonstrated a better LCSS against the sublobectomy in stage I SCC. SCC with sizes of >2 to ≤3 cm could become a pretty good indicator for lobectomy, while a sublobectomy may be an adequate substitute when the SCC size is ≤2 cm, especially for patients who cannot tolerate a lobectomy. T1c category can also suggest a lobectomy instead of sublobectomy for stage I SCC patients.